Influence of governance institutions on households' willingness to pay for resources conservation in Khalong-la-Lithunya wetland area Lesotho - Mungatana, Eric D. (University of Pretoria, 2017)
Dissertation (MSc (Agric))--University of Pretoria, 2017.